KAJIAN YURIDIS PROGRAM PENERBITAN SERTIPIKAT HAK ATAS TANAH ELEKTRONIK - Agustina, Enny (Faculty of Law, University of Palembang, 2021)
This study discusses how the juridical study of the electronic land rights certificate issuance program and how the mechanism in the issuance of electronic land rights certificates. This research method is normative legal research with a statutory approach, by reviewing regulations related to legal issues. The result of this research is the juridical aspect of issuing electronic certificates is contained in the Minister of ATR/Head of BPN Regulation Number 1 of 2021. In Article 1 number 8 of the Ministerial Regulation defines electronic certificates as